CIVILIZATIONAL JURISPRUDENCE: A RESPONSE TO THE LOGICAL FALLACIES OF THE JURISPRUDENCE IDEOLOGY NARRATIVES OF ANTI-PANCASILA ORGANIZATIONS ON SOCIAL MEDIA - Ahmad Rifqi Muchtar; Ali Wafa' (SOSIOEDUKASI, 2025)
This research responds to the growing movement among certain Islamic mass organizations (Ormas) in Indonesia that continue to challenge the legitimacy of Pancasila as the state ideology by using the framework of civilization jurisprudence (fikih peradaban). These groups argue that Pancasila does not sufficiently accommodate Islamic law (syariah), which they claim should be prioritized as the legal foundation for a Muslim-majority nation. To critically examine these claims, this study employs content analysis to uncover the logical fallacies embedded within the ideological narratives produced by these Ormas. Primary data consist of written and digital narratives from organizations such as Hizbut Tahrir Indonesia (HTI), the Islamic Defenders Front (FPI), Jama'ah Ansharut Daulah (JAD), and Jama'ah Islamiyah—groups known to have transnational ideological affiliations, including links to ISIS. These narratives are sourced from official websites, organizational documents (such as constitutions and bylaws), and social media postings. Secondary data include reports from the Ministry of Home Affairs and the Ministry of Religious Affairs, as well as authoritative Islamic scholarly sources such as classical fiqh, usul fiqh, tafsir ahkam, academic journals, and credible news articles. The analysis reveals that the discourse promoted by these transnational Islamic groups frames Pancasila and the Quran as mutually exclusive, leading to an erroneous ideological dichotomy. Their reasoning is shown to be fallacious due to inappropriate comparisons, overgeneralizations, and the failure to understand the distinct epistemic categories between divine revelation and a contextual national ideology. The study concludes that fikih peradaban offers a constructive paradigm for harmonizing religious and national commitments, affirming that Indonesian law is inherently dynamic, contextual, and capable of integrating universal Islamic values without undermining Pancasila.